Pengaruh Motivasi Terhadap Kinerja Pegawai Dengan Kepuasan Sebagai Variabel Intervening Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Sukoharjo - Nur Fajar Ali Maulana; Esti Dwi Rahmawati; Nur Hadi (Manajemen Kreatif Jurnal, 2024)
The aim of this research is to partially determine whether motivation has a significant effect on employee performance, motivation has an effect on job satisfaction, job satisfaction has an effect on performance, and whether job satisfaction mediates work motivation on employee performance. This research was conducted quantitatively using an explanatory and descriptive approach and data collection through questionnaires. A total of 40 employees of the Sukoharjo Regency Satu Pindu Investment and Integrated Services Service consist of 27 civil servants, 3 PPPK and 10 freelance daily workers (THL). Regression correlation analysis was used. The results of the analysis show that work motivation has a significant effect on performance and job satisfaction, job satisfaction has a significant effect on performance and job satisfaction has succeeded in mediating work motivation on employee performance.